Nepal’s Survival Strategies During the Shah Era - Subba, Phanindra (Unity Journal, 2021)
Nepal is one of the few countries in the world which was never colonized during the hey-day of colonial era. She is bounded on the north by China and on the three other sides by India. Compared to these Colossi, Nepal is significantly weaker in terms of demography, economics, military strength and physical size. Nepal is, thus, a typical small state. There are several strategies that small states can employ to compensate for their weaknesses, ensure security, and secure a measure of influence over other actors. Small state literature exposes that such states can choose from strategies such as entering into alliance with a great power, hedging, neutrality, balancing, and band– wakening. Currently, this paper explores a trajectory of survival strategies that Nepal adopted during the Shah era on the basis of the analysis of crucial events that occurred during this period from perspectives of small state theories. The paper is based on the study of relevant books, documents and articles on small states amidst international affairs in global spheres. The joint rise of India and China is transforming the strategic landscape of Nepal’s neighborhood and will have a profound and long-term impact on Nepal. Nepal in the past has demonstrated a stubborn ability to survive by adapting to changing geopolitical situations. Although the present-day world is far more complex, lessons from the past are worth reconsidering because there are instances of similarities to the present. Furthermore, some aspects of strategy are constant.